Climate change impact assessment on three major crops in the north-central region of Bangladesh using DSSAT - Rahman, Atikur; Mojid, Mohammad Abdul; Banu, Selina (International Journal of Agricultural and Biological Engineering, 2018)
The potential consequences of climate change emanated from global warming are very alarming; the greatest concern is the potentially disastrous consequences on crop agriculture and food security in many parts of the world. Bangladesh is a country highly susceptible to climate change, but information in this regard is still inadequate. This study investigated the effects of climate change on three major crops – wheat, potato and rice – in the north-central region of Bangladesh. Two climate change scenarios, A2 and B2, of the Intergovernmental Panel on Climate Change (IPCC) were generated by employing MAGICC/SCENGEN model together with the observed climate data of the region. The growth and yield of the crops were simulated using DSSAT CERES-Wheat, SUBSTOR-Potato and CERES-Rice models under the present and projected future changing climatic conditions. For a predicted 5.32ºC increase in temperature in the year 2100, the yield of wheat, rice and potato would decrease by 47.6%, 67.8% and 38.6%, respectively. The increased temperature would accelerate physiological maturity of the crops as reflected by their reduced length of growing season (LGS) by 1.20% to 18.5%. The reduced LGS would reduce seasonal evapotranspiration (ET) of the crops by shortening time-span for ET generation. Due to dominant yield reduction over ET reduction, the water use efficiency (WUE) for grain/tuber and biomass yields would decrease with the changing climate. The reduced crop yields are an indicative of a potential future risk of food security in Bangladesh. The results of this study can therefore guide to adopt coping mechanisms in the light of climate change to ensure future food security of the country.Keywords: climate change, DSSAT, MAGICC/SCENGEN model, CERES model, SUBSTOR model, growing season length, crop-water useDOI: 10.25165/j.ijabe.20181104.3331Citation: Rahman A, Mojid M A, Banu S. Climate change impact assessment on three major crops in the north-central region of Bangladesh using DSSAT. Int J Agric & Biol Eng, 2018; 11(4): 135-143.